Application of EDA methodology for assessment of the rotating machines insulation system condition - Ilić, Denis M; Partonjić, Radmila; Milić, Momčilo; Jovanović, Djordje; Nikolić, Ljubiša (Proceedings, Electrical engineering institute "Nikola Tesla", 2016)
The insulation system of rotating machines of high importance has always been the object of thorough screening with certified test methods that are getting constantly improved. Low-power machines and “less important” machines like high voltage motors, are rarely subjected to detailed electrical tests because of low resources allocated for their maintenance. The introduction of the EDA methodology in practice creates the conditions for reliable and complete diagnostics of stator windings of big machines, as well as the fast, easy and inexpensive screening for low-power machines (i.e. HV motors). The aim of the paper is to present the EDA methodology and its possibilities, including the solutions within the hardware and software